2020
DOI: 10.14720/aas.2020.116.1.1116
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles alleviate cadmium toxicity in lentil (Lens culinaris Medic) seeds

Abstract: This research was carried out with the aim of investigating the effects of different concentrations of titanium dioxide nanoparticles and cadmium on lentil seed germination and seedling early growth. The experiment was conducted as a factorial layout based on a completely randomized design with four replicates. Test plants were exposed to 0, 100, 250, and 500 ppm of cadmium, and then amended with 0, 100, 200, and 300 ppm of TiO2 nanoparticles. Results demonstrated that the application of 300 ppm of titanium di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…However, this influence is more significant under water stress conditions because of the limited supply of water in this situation. The combination of titanium dioxide nanoparticles and selenium dioxide nanoparticles accelerates seed germination and seedling growth at a notable level [11,29,35,36,38]. In other research, titanium dioxide nanoparticles increased the lentil seedling length [11].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, this influence is more significant under water stress conditions because of the limited supply of water in this situation. The combination of titanium dioxide nanoparticles and selenium dioxide nanoparticles accelerates seed germination and seedling growth at a notable level [11,29,35,36,38]. In other research, titanium dioxide nanoparticles increased the lentil seedling length [11].…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, it has been reported that treating seeds with proper organic or inorganic compounds before planting, which is normally called pretreatment or priming, can improve the seed germination quality and quantity under different conditions compared to nontreated seeds [7,8]. Pretreatment of seeds is a simple and inexpensive but successful method to improve seed germination [9][10][11]. Other researchers claimed that seed pretreatment could also improve the germination and emergence percentage of seeds [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have evaluated NP effects on lentil production. These include biosynthesized Au-NPs [ 57 ], SiO 2 -NPs [ 58 ], TiO 2 -NPs [ 59 ], ZnO-NPs [ 60 ] and Ag-NPs [ 61 ]. The studies, however, do not consider the changes in content of nutrients such as minerals which affect final lentil seed quality.…”
Section: Resultsmentioning
confidence: 99%